2017
DOI: 10.3390/ijms18040821
|View full text |Cite
|
Sign up to set email alerts
|

Histogram Analysis of Diffusion Weighted Imaging at 3T is Useful for Prediction of Lymphatic Metastatic Spread, Proliferative Activity, and Cellularity in Thyroid Cancer

Abstract: Pre-surgical diffusion weighted imaging (DWI) is increasingly important in the context of thyroid cancer for identification of the optimal treatment strategy. It has exemplarily been shown that DWI at 3T can distinguish undifferentiated from well-differentiated thyroid carcinoma, which has decisive implications for the magnitude of surgery. This study used DWI histogram analysis of whole tumor apparent diffusion coefficient (ADC) maps. The primary aim was to discriminate thyroid carcinomas which had already ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 28 publications
4
67
1
Order By: Relevance
“…The results of this study indicated that the repeatability of IVIM parameters is excellent when using W-L ROI analysis for thyroid nodules, providing a strong basic foundation for future multi-centre, large-sample studies as well as stratification research. These results revealed that the diffusion effect plays a major role in differentiating malignant thyroid nodules, which may be based on differences in the cell density and histopathologic features of benign and malignant thyroid nodules [18,35]. Some ADC and DKI studies with higher b values (1000 s/mm 2 to 2000 s/mm 2 ) have shown the role of diffusion in differentiating benign from malignant thyroid nodules [36,37].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The results of this study indicated that the repeatability of IVIM parameters is excellent when using W-L ROI analysis for thyroid nodules, providing a strong basic foundation for future multi-centre, large-sample studies as well as stratification research. These results revealed that the diffusion effect plays a major role in differentiating malignant thyroid nodules, which may be based on differences in the cell density and histopathologic features of benign and malignant thyroid nodules [18,35]. Some ADC and DKI studies with higher b values (1000 s/mm 2 to 2000 s/mm 2 ) have shown the role of diffusion in differentiating benign from malignant thyroid nodules [36,37].…”
Section: Discussionmentioning
confidence: 87%
“…The results derived from the S-S ROI analysis showed variability in both sensitivity and specificity [6,7]. Whereas some studies have used W-L ADC imaging or histograms to evaluate thyroid nodules and distinguish different types of malignant thyroid nodules or benign nodules from malignant nodules [18][19][20], this study used IVIM with W-L ROI delineation that included cystic, necrotic and micro-calcified components of thyroid nodules, and the results demonstrated that all parameters had better reproducibility and repeatability than those of S-S ROI delineation. Notably, the perfusionrelated parameters (f and D*) derived from the W-L ROIs showed excellent intra-and interobserver agreement, which may be related to the use of ROIs across whole tumours, thus minimizing the intra-and interobserver differences in ROI delineations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown a significant inverse correlation between tumor cell density and ADC value in PCNSLs, suggesting ADC to be a surrogate marker for tumor proliferation and Ki-67 index [23][24][25]. Barajas et al [11] reported that ADC measurements could predict clinical prognosis in patients with PCNSLs.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity in the malignant tissues is recognized to reflect cellularity, necrosis, and angiogenesis, which are associated with disorders of attenuation [33]. Previous studies demonstrated that texture analysis of images obtained from US and MRI is useful for distinguishing between benign thyroid nodules and malignancies with less-uniform texture parameters, classifiers, and applications [15,16,[34][35][36]. Since thyroid nodules are often detected by CT scan before performing further US, with texture analysis using DECT, unnecessary further examinations of the thyroid lesions can be potentially prevented.…”
mentioning
confidence: 99%